AN An Analysis Of The English Textbook "English In Mind Second Edition" Based On The Merdeka Curriculum - Voni Nuralawiah; Syafrizal Syafrizal; Akhmad Baihaqi (Journal on Education, 2024)
This study aims to analyze the accordance of the content of the English textbook "English in Mind Second Edition" based on learning outcomes by the Merdeka curriculum, namely Listening-Speaking, Reading-Viewing, and Writing-Presenting. This research used qualitative research with content analysis methods and used documentation, questionnaires, and interviews to collect data. The findings of this study concluded that the English textbook includes about 41% of material relevant to the Listening-Speaking element, 31% of the material pertinent to the Reading-Viewing element, and 28% of the material appropriate to the Writing-Presenting element. This means that the English textbook as a whole is in accordance with the Merdeka curriculum. Based on student questionnaires about the elements of learning outcomes in textbooks, there are elements of listening, speaking, reading, viewing, writing, and presenting in textbooks. Then, for interviews with teachers, the textbook is in accordance with the learning outcomes in the Merdeka curriculum. However, no one learns about the Indonesian nation, for example, knowledge and culture, so this book is not recommended as a sourcebook but as a supplementary book. It can be concluded that based on these findings, the textbook "English in Mind Second Edition" is in accordance with the Merdeka curriculum as a supplementary book.